When an economy grows around 2% for decades, is it a structural problem? Production functions - Ledesma, Dora; Hernández, Lidia; Muciño, Teresa (Archives of Business Research, 2021)
Mexico for decades has grown around 2% annually, increasing informal employment and poverty. Neoliberalism brought benefits to certain sectors of society but widened the wage gap between households. In recent years, the structural reforms proposed by the government to lift Mexico from its economic slumber have caused controversy. Twenty years ago it was believed that NAFTA would activate the economy and improve the standard of living of all Mexicans, but it did not. Applying optimization techniques in the production functions under scenarios, this work shows the structure of the economy and its impacts on households, mainly. A look at what has been happening.